Expression of endothelin-1 and endothelin-1 receptor A in canine mammary tumours. (June 2015) - Restucci, B.; Martano, M.; Maiolino, P.
Highlights: Evaluation of ET-1 and ETA R expression in canine mammary tumours. Increase of expression from benign tumours to G1 and G2 carcinomas. Positive co-localization in benign mammary tumours and in G1 and G2 carcinomas. Decrease of expression and negative co-localization in G3 carcinomas. Abstract: Endothelins and their receptors have been implicated in numerous diseases and have recently emerged as relevant players in a variety of malignancies. Tumours overexpress the Endothelin-1 (ET-1) and the Endothelin-A receptors (ETA R) and their interaction enhances tumour growth and metastasis by promoting tumour cell survival, proliferation and angiogenesis. In this study we have evaluated the expression of ET-1 and ETA R in 50 canine mammary tumours, compared to normal controls. Results demonstrated a progressive increase in ET-1 and ETA R expression from benign tumour to grade 1 and to grade 2 malignant mammary tumours with a decrease of expression in grade 3 carcinomas. Co-localization of ET-1 and ETA R was observed in benign mammary tumours and in G1 and G2 carcinomas, while absent in G3 carcinomas. Concluding, ET-1/ETA R can be considered reliable markers for evaluating malignancy of canine mammary tumours and could have importance for the development of specific anticancer therapies.